2022
DOI: 10.1111/irv.13031
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus disease burden in adults aged 60 years and older in high‐income countries: A systematic literature review and meta‐analysis

Abstract: Background: Respiratory syncytial virus (RSV)-associated acute respiratory infection (ARI) is an underrecognized cause of illness in older adults. We conducted a systematic literature review and meta-analysis to estimate the RSV disease burden in adults ≥60 years in high-income countries.Methods: Data on RSV-ARI and hospitalization attack rates and in-hospital case fatality rates (hCFR) in adults ≥60 years from the United States, Canada, European countries, Japan, and South Korea were collected based on a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
114
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(127 citation statements)
references
References 56 publications
11
114
1
1
Order By: Relevance
“…In the United Kingdom, RSV-attributable respiratory disease is estimated to cause 83 paediatric deaths per average season [ 2 ]; this rises to 8482 deaths per year among adults aged ≥18 years, with 93% of those cases occurring in older adults aged ≥65 years [ 3 ]. A recent meta-analysis estimated that 5.2 million cases of RSV occurred in high-income countries among adults aged ≥60 years in 2019, leading to 470,000 hospitalisations and 33,000 in-hospital deaths [ 4 ]. Limited epidemiological data are available for developing countries [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United Kingdom, RSV-attributable respiratory disease is estimated to cause 83 paediatric deaths per average season [ 2 ]; this rises to 8482 deaths per year among adults aged ≥18 years, with 93% of those cases occurring in older adults aged ≥65 years [ 3 ]. A recent meta-analysis estimated that 5.2 million cases of RSV occurred in high-income countries among adults aged ≥60 years in 2019, leading to 470,000 hospitalisations and 33,000 in-hospital deaths [ 4 ]. Limited epidemiological data are available for developing countries [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis estimated that 5.2 million cases of RSV occurred in high-income countries among adults aged ≥60 years in 2019, leading to 470,000 hospitalisations and 33,000 in-hospital deaths [ 4 ]. Limited epidemiological data are available for developing countries [ 4 , 5 ]. These figures are likely to be underestimated as they only consider those admitted to hospital, omitting those without access to care and those with suboptimal healthcare-seeking behaviour [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The virus is not only a threat to infants but also to adults with comorbidities as well, especially individuals with chronic cardiopulmonary diseases [ 73 ]. Furthermore, most recent meta-analyses revealed that RSV-related case fatality proportions for individuals over 60 years of age residing in developed countries was approximately 8% [ 74 ], with an estimated 33,000 in-hospital deaths due to acute RSV infection [ 75 ].…”
Section: Respiratory Syncytial Virus (Rsv)mentioning
confidence: 99%
“…Human orthopneumovirus (previously known as the respiratory syncytial virus (RSV)) is another serious respiratory pathogen that is frequently a cause of hospital admissions related to bronchitis, bronchiolitis, and pneumonia, particularly in children, seniors, or immunocompromised patients [ 11 , 12 , 13 ]. In 2019, RSV infection, including only ≥60-year-old adults in high-income countries, was estimated to encompass approximately 5 million cases, including 33,000 in-hospital deaths [ 14 ]. These findings show the impact of SARS-CoV-2, FluV, and RSV seasonality on the global burden of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%